Hypoxia Response Element-Directed Expression of aFGF in Neural Stem Cells Promotes the Recovery of Spinal Cord Injury and Attenuates SCI-Induced Apoptosis - Ying, Yibo; Zhang, Yifan; Tu, Yurong; Chen, Min; Huang, Zhiyang; Ying, Weiyang; Wu, Qiuji; Ye, Jiahui; Xiang, Ziyue; Wang, Xiangyang; Wang, Zhouguang; Zhu, Sipin (Frontiers in Cell and Developmental Biology, 2021)
Reducing neuronal death after spinal cord injury (SCI) is considered to be an important strategy for the renovation of SCI. Studies have shown that, as an important regulator of the development and maintenance of neural structure, acidic fibroblast growth factor (aFGF) has the role of tissue protection and is considered to be an effective drug for the treatment of SCI. Neural stem cells (NSCs) are rendered with the remarkable characteristics to self-replace and differentiate into a variety of cells, so it is promising to be used in cell transplantation therapy. Based on the facts above, our main aim of this research is to explore the role of NSCs expressing aFGF meditated by five hypoxia-responsive elements (5HRE) in the treatment of SCI by constructing AAV–5HRE–aFGF–NSCs and transplanting it into the area of SCI. Our research results showed that AAV–5HRE–aFGF–NSCs can effectively restore the motor function of rats with SCI. This was accomplished by inhibiting the expression of caspase 12/caspase 3 pathway, EIF2α–CHOP pathway, and GRP78 protein to inhibit apoptosis.